Politics of Representation in 18th-century England & France: The Case of Le Chevalier de Saint-Georges - Thomas, Jesse (Alternative francophone)

(untitled) (University of Alberta, Department of Modern Languages and Cultural Studies, 2025)
A surprising majority of the existing images of Joseph Bologne, Le Chevalier de Saint-Georges, were created during a short period from 1789- 1791, and are essentially the result of his visit to London for a fencing exhibition match organized for the Prince of Wales by the Duc d’Orleans and his political operatives. The scarcity of French- origin images of Le Chevalier, so celebrated during his lifetime in France as a musician, composer, musical director, and fencing master, is perplexing. Why is this the case? Perhaps it can be explained in part by the French visual culture at the time, characterized by censorship and intolerance in the visual arts, in stark contrast to a popular print culture in England that tolerated political and social commentary and even satire, creating a market for prolific production and enthusiastic consumption by the British public.